Proinflammatory and proapoptotic markers in relation to mono and di-cations in plasma of autistic patients from Saudi Arabia - El-Ansary, Afaf K (BioMed Central, 2011)
OBJECTIVES: Autism is a developmental disorder characterized by social and emotional deficits, language impairments and stereotyped behaviors that manifest in early postnatal life. This study aims to clarify the relationship amongst absolute and relative concentrations of K(+), Na(+), Ca(2+), Mg(2+ )and/or proinflammatory and proapoptotic biomarkers. MATERIALS AND METHODS: Na(+), K(+), Ca(2+), Mg(2+), Na(+)/K(+), Ca(2+)/Mg(2+ )together with IL6, TNFα as proinflammatory cytokines and caspase3 as proapoptotic biomarker were determined in plasma of 25 Saudi autistic male patients and compared to 16 age and gender matching control samples. RESULTS: The obtained data recorded that Saudi autistic patients have a remarkable lower plasma caspase3, IL6, TNFα, Ca(2+ )and a significantly higher K(+ )compared to age and gender matching controls. On the other hand both Mg(2+ )and Na(+ )were non-significantly altered in autistic patients. Pearson correlations revealed that plasma concentrations of the measured cytokines and caspase-3 were positively correlated with Ca(2+ )and Ca(2+)/K(+ )ratio. Reciever Operating Characteristics (ROC) analysis proved that the measured parameters recorded satisfactory levels of specificity and sensitivity. CONCLUSION: Alteration of the selected measured ions confirms that oxidative stress and defective mitochondrial energy production could be contributed in the pathogenesis of autism. Moreover, it highlights the relationship between the measured ions, IL6, TNFα and caspase3 as a set of signalling pathways that might have a role in generating this increasingly prevalent disorder. The role of ions in the possible proinflammation and proapoptic mechanisms of autistics' brains were hypothesized and explained.